The effectiveness of specific rondo-style drills in the offensive performance of futsal players - Daham, Asst.L.Mirand Mtanes; Hussein, L.Dr. Raad Ali; Kazem, Prof. Dr. Haitham Mohammed (Sulaimani Journal for Humanities, 2026)
Futsal requires constant mental focus during matches, unlike other sports, because it has specific demands, a high-tempo style of play, and various variables and situations due to the small size of the field and the speed of play. Therefore, researchers began implementing specific rondo-style drills to create a suitable and effective environment that closely resembles competitive situations. These drills were implemented using the rondo technique, which is completely different from the methods players are accustomed to, as it requires mental engagement with continuous and effective performance that cannot be interrupted or slowed down. This is especially true since these drills are linked to the rondo technique and its various offensive aspects. The rondo technique is a modern training method recently adopted in the world of football by advanced clubs and national teams. It contributes significantly and effectively to ball possession and playing a comprehensive style of football, occupying different areas of the field through movement and changing player positions within specific zones and geometric shapes (circles, squares, or rectangles). This enables the team to control the flow of the match in a way that suits the team's objectives. The experimental method, employing two equivalent groups, was used to complete the research procedures, which lasted for several months, to improve the offensive performance of the player and the team. The aim was to prepare them for various playing situations that demand high performance, speed, and accuracy in executing tasks, maintaining possession of the ball, and avoiding easy loss of possession for as long as possible, even under pressure from teammates. The main objective of the research was to determine the effectiveness of specific rondo-style drills on the offensive performance of futsal players. The research results were encouraging, showing an improvement in the offensive performance of the players who participated in the specialized futsal drills.